Rancang Bangun Sistem Informasi Pengolahan Data Modul Dan Jadwal Praktikum Berbasis Website - Victor Ohoiwurun; Emy L. Tatuhey (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
The development of information technology provides great benefits for society, especially in terms of information. STIMIK Sepuluh Nopember Jayapura is one of the private campuses in the city of Jayapura which has a computer laboratory, the STIMIK Sepuluh Nopember Jayapura computer laboratory provides facilities for students to develop skills in information and communication technology. However, the system used today still has deficiencies in displaying schedule information and practicum modules. Therefore, it is necessary to build a website-based information system that can be useful in displaying schedule and module information clearly and easily understood. The development method uses the prototype method, the data collection method uses the interview method, observation and literature study the design method uses a structured method with context diagrams, and the database description uses ERD and this system is built using the PHP programming language and the database used is MySQL. This information system is based on an online website where the output results are in the form of operators being able to access the information system and input module data and schedules so that students can view or download practicum module data along with the particum schedule. Based on the results of the Black Box testing, all system functions can run properly or 100% valid, so that the module data processing information system and practicum schedule are in accordance with what is expected by the user and the user can access information about the module along with the practicum schedule in real time and it is easier to used.